2019
DOI: 10.1007/s10336-019-01645-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of novel ornamental traits and the establishment of sexual dimorphism: insights from domestic birds

Abstract: The evolution of sexually monomorphic ornamental traits is poorly understood and may require a shift in research focus away from strict sexual selection. To properly understand how selection affects such traits, we need to know to what extent they are constrained by their genetic architecture. Specifically, we need to understand how and in what state (monomorphic or dimorphic) ornamental traits first appear, how they are subsequently rendered sexually dimorphic, or not, and what mechanisms underlie their furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Lande's process could still occur over shorter timescales, and thus be invisible on a phylogeny. For instance, multiple novel ornaments in domestic birds have arisen monomorphically over evolutionary timescales of a few thousand generations that are consistent with Lande's two‐step model, (Kraaijeveld ).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Lande's process could still occur over shorter timescales, and thus be invisible on a phylogeny. For instance, multiple novel ornaments in domestic birds have arisen monomorphically over evolutionary timescales of a few thousand generations that are consistent with Lande's two‐step model, (Kraaijeveld ).…”
Section: Discussionmentioning
confidence: 58%
“…Guo et al. () document that elongated head‐feathers on several breeds of domestic chickens arise from an allele that affects expression of the gene HOXB8 (Kraaijeveld ). The rectricial feather follicle is responsive to sex hormones (Yu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex hormones such as androgen may indirectly influence the expression of androgen-regulated genes, through binding to transcription factors that interact with regulatory elements such as enhancer and cause sex-biased gene expression, which leads to sex-specific phenotypes ( Coyne et al 2008 ; Mank 2009 ). Whereas male plumage appears to be testosterone-dependent in passerines ( Kimball 2006 ), the molecular mechanisms controlling sex-biased gene expression and development of sexually dimorphic traits in birds is largely unknown ( Kraaijeveld 2019 ; Gazda et al 2020a ). In this study, we identified potential TFs that may regulate the expression of the red plumage color gene CYP2J19 .…”
Section: Resultsmentioning
confidence: 99%
“…A huge body of literature on how both sexual and natural selection can lead to speciation has been published [26,27] but almost nothing is known about the genetic basis of male ornaments or male "weapons" used in male-male competition [28,29]. To identify the genes on which female preferences act on is an important task that is necessary to permit the testing of hypotheses regarding the roles of sexual selection at the molecular genetic level.…”
Section: Introductionmentioning
confidence: 99%